Strategi Pengembangan Pantai Manggar sebagai Destinasi Wisata Unggulan di Kota Balikpapan - M. Harry Mulya Zein; Sekar Dwi Astuti; Sisca Septiani (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study examines the role of the Youth, Sports, and Tourism Office in developing Manggar Beach as a leading tourist destination in Balikpapan City. Using Pitana and Gayatri's theory on the role of government as a motivator, facilitator, and dynamic, this study uses a qualitative descriptive approach with data collection through observation, interviews, and documentation. The results of the study indicate that the office has implemented various strategies such as digital promotion, facility development, and stakeholder collaboration with the pentahelix concept. However, there are still challenges in the form of suboptimal facility maintenance, waste management problems, and relatively high entrance ticket prices. The office has responded with initiatives such as cleanliness campaigns, periodic ticket price evaluations, and creative economy development to increase competitiveness. This study contributes to the understanding of the dynamics of the role of local government in developing sustainable tourism for coastal destinations.